2021
DOI: 10.1021/acsomega.1c04230
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Activity of Ficusonolide, a Triterpene Lactone from Ficus foveolata (Wall. ex Miq.): In Vitro, In Vivo, and In Silico Approaches

Abstract: Diabetes is a chronic condition which is locally managed through the stem of Ficus foveolata. To find the exact chemical constituent responsible for this activity, a triterpene lactone (ficusonolide) isolated from F. foveolata was studied for antidiabetic potential through the in vitro antidiabetic paradigm employing L-6 cells and an in vivo antidiabetic assay against non-insulin-dependent rats. The results on glucose uptake in the L-6 cell line indicated that ficusonolide has enhanced the uptake of glucose by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Our previous study on catechin isolated from methanol extract of the stem bark of C. fistula showed the same kind of impact in the pancreases of STZ-induced diabetic rats, and we concluded that they possessed insulin mimetic activity [21]. Other studies investigated using diabetes rat models with pentacyclic triterpenoids, oleanolic acid, gymnemic acid IV, ursolic acid and ficusonolide exhibited pharmacological properties including improved insulin secretion and signaling via important transduction pathways, restored β-cell function, reduced hyperglycemia and increased glucose uptake in skeletal muscles [22][23][24]. Triterpenoid saponins from Primula denticulate were reported to potentially possess glucose-lowering properties in STZ-induced diabetic rats [25].…”
Section: Discussionmentioning
confidence: 79%
“…Our previous study on catechin isolated from methanol extract of the stem bark of C. fistula showed the same kind of impact in the pancreases of STZ-induced diabetic rats, and we concluded that they possessed insulin mimetic activity [21]. Other studies investigated using diabetes rat models with pentacyclic triterpenoids, oleanolic acid, gymnemic acid IV, ursolic acid and ficusonolide exhibited pharmacological properties including improved insulin secretion and signaling via important transduction pathways, restored β-cell function, reduced hyperglycemia and increased glucose uptake in skeletal muscles [22][23][24]. Triterpenoid saponins from Primula denticulate were reported to potentially possess glucose-lowering properties in STZ-induced diabetic rats [25].…”
Section: Discussionmentioning
confidence: 79%
“…Our observations align seamlessly with the previous research, exemplified by the study conducted by Pwaniyibo et al [26], which demonstrated the inherent antidiabetic efficacies prevalent in an array of Ficus species, thereby alluding to a plausible variation in bioactive compounds (flavonoids, glycosides, alkaloids, saponins, tannins, terpenes, carotenoids, and steroids) contingent upon the specific species. Notwithstanding our primary emphasis on polyphenols and flavonoids, the research delineated by Din et al [27] broadened the academic discourse by elucidating the antidiabetic attributes of a specific triterpene lactone, sourced from Ficus, thereby highlighting the expansive array of therapeutic compounds within this genus. Concurrently, Lin et al [28] provided insights into an alternative extraction modality for Ficus carica leaves to alleviate diabetic mice and raise psoralen and umbelliferone which have substantial glucose-lowering activity.…”
Section: Discussionmentioning
confidence: 99%
“…Docking studies have been carried out on several triterpenes to determine their binding modes. Ficusonolide, a triterpene lactone isolated from Ficus foveolata, showed strong interaction when docked into the active sites of PTP1B, dipeptidyl peptidase-IV, α-amylase, and α-glucosidase [ 51 ]. Another computational study reported lupeol’s allosteric inhibitory activity on PTP1B.…”
Section: Discussionmentioning
confidence: 99%